2013
DOI: 10.1155/2013/748241
|View full text |Cite
|
Sign up to set email alerts
|

Caseous Necrosis of Mitral Annulus: A Rare Cause of Stroke

Abstract: The current report describes a rare case of a caseous necrosis presenting as a pseudotumor in ventricle, revealed by stroke. Cerebral MRI, showing multiples lacunes, evocates a cardioembolic mechanism. Transthoracic and transesophageal echocardiography demonstrate a large hyperechogenic mass fixed to the posterior mitral valve and annulus while thoracic tomography revealed a fully calcified lesion, at the mitral annulus, evocative of caseus necrosis. Medical therapy was preferred (anticoagulation), because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…There is no consensus on the best therapy, and some authors also suggest anticoagulant therapy, in particular when there is communication between CCAM and systemic circulation [15,24]. This therapeutic option is interesting as it is reported that MAC and CCAM could be associated with atrial fibrillation [5].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the best therapy, and some authors also suggest anticoagulant therapy, in particular when there is communication between CCAM and systemic circulation [15,24]. This therapeutic option is interesting as it is reported that MAC and CCAM could be associated with atrial fibrillation [5].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The mechanisms for the occurrence of stroke are unclear; it is unknown whether they occur due to their association with atherosclerosis, age and other risk factors related to the patients, or embolization of fragments of the mass. 6 The differential diagnoses include intracardiac tumors, especially atrial myxoma, thrombosis of the coronary sinus, circumflex artery anomalies, and vegetations and abscesses of the mitral annulus.…”
Section: 25mentioning
confidence: 99%
“…[6][7][8] The mechanisms for the occurrence of stroke are unclear; it is unknown whether they occur due to their association with atherosclerosis, age and other risk factors related to the patients, or embolization of fragments of the mass. 6 The differential diagnoses include intracardiac tumors, especially atrial myxoma, thrombosis of the coronary sinus, circumflex artery anomalies, and vegetations and abscesses of the mitral annulus. 1,9,10 Multiple modalities of cardiovascular imaging should be used to differentiate between the various lesions and, in these cases, are capable of establishing a definitive diagnosis without requiring pathological analysis of the mass, eliminating invasive surgical procedures.…”
Section: 25mentioning
confidence: 99%
“…However, there is no consensus on the optimal management for CCMA, as stated by Elgendy and Conti [13] in a recent review article. The authors suggest that, in most cases, conservative management for this lesion is sufficient, and that anticoagulation should be considered only in patients with CCMA who present with embolic manifestations [18, 22, 28]. In contrast, several authors recommend surgical intervention for associated mitral valvular dysfunction (either stenosis or regurgitation), embolic manifestations, or when it is impossible to rule out the possibility of a tumor.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Although anticoagulant therapy has been considered for some of these patients, anticoagulation is ineffective to prevent a cardioembolic stroke in these patients. As suggested by Corre and colleagues [28], further studies are needed to resolve the optimal treatment to decrease the risk of embolization in patients with CCMA. Thus, it is important to differentiate CCMA from MAC.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%